Postharvest Biology and Technology of Temperate Fruits - Mir, Shabir Ahmad; Shah, Manzoor Ahmad; Mir, Mohammad Maqbool; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This edited volume provides insight into temperate fruits, with an emphasis on postharvest physiology, storage, packaging and technologies for maintaining fruit quality. Chapters are devoted to individual fruits and focus on fundamental issues such as methods for maintaining or enhancing quality, minimizing postharvest losses, and recommended technologies to boost demand. Contributions come from experts in the field, making this a key reference for all aspects of postharvest management of temperate fruits. The volume is unique in its focus on the biodiversity, nutritional and health benefits, and postharvest technologies for shelf life enhancement of temperate fruits. Contributing authors address the postharvest biology and technology of individual temperate fruits such as plum, cherry, peach, apricot, apple, pear, quince, loquat, kiwi, persimmon and berries. There has been tremendous growth in the research and development of new techniques to maintain the quality of temperatefruits from farm to table. Contributions from experts in the field cover these recent advances, providing up-to-date and relevant information for researchers, postharvest/fruit technologists, food scientists, postgraduate students, and others working in the industry.
Diversity and production of temperate fruits -- Orchard management of temperate fruits -- Nutritional and health benefits of temperate fruits -- Postharvest technologies for shelf life enhancement of temperate fruits -- Postharvest Biology and Technology of Plum -- Postharvest Biology and Technology of Cherry -- Postharvest Biology and Technology of Peach -- Postharvest Biology and Technology of Apricot -- Postharvest Biology and Technology of Apple -- Postharvest Biology and Technology of Pear -- Postharvest Biology and Technology of Quince -- Postharvest Biology and Technology of Loquat -- Postharvest Biology and Technology of Kiwi -- Postharvest Biology and Technology of Strawberry -- Postharvest Biology and Technology of Berries -- Postharvest Biology and Technology of Persimmon -- Food safety management of temperate fruits from farm to fork.
Keywords: Food science; Botany; Security systems; Food Science; Plant Science; Security Science and Technology